1993
DOI: 10.3109/10611869308996085
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Biophysical-Kinetic Model to Understand the Roles of Protein Binding and Membrane Partitioning on Passive Diffusion of Highly Lipophilic Molecules Across Cellular Barriers

Abstract: The novel antioxidants U-78517F and U-74006F, or lazaroids, are highly lipophilic organic molecules with poor brain uptake. To understand this paradoxical behavior better, continuous monolayers of Madin-Darby canine kidney (MDCK) epithelial cells with distinct apical (AP) and basolateral (BL) plasma membrane domains grown on polycarbonate membrane filters and plastic were used to examine the mechanism of transcellular diffusion. Independent kinetic experiments were used to quantify AP to BL flux, efflux from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…1, II and III) arising from CA-based and OMCA-based cyclic prodrugs seem to also be a significant problem with these linkers, modified linkers having more rapid rates of conversion of the intermediate(s) to DADLE are also being developed in our laboratory. Plasma protein binding can exert a significant influence on the pharmacokinetic properties and biological activities of a drug, especially for brain-targeted compounds (Raub et al, 1993). For DADLE and its prodrugs, more lipophilic compounds had higher fractions bound in the order CA-DADLE Ͼ OMCA-DADLE Ͼ AOA-DADLE Ͼ DADLE, but none of the prodrugs had protein-binding values high enough to substantially affect the distribution of the compounds.…”
Section: Discussionmentioning
confidence: 99%
“…1, II and III) arising from CA-based and OMCA-based cyclic prodrugs seem to also be a significant problem with these linkers, modified linkers having more rapid rates of conversion of the intermediate(s) to DADLE are also being developed in our laboratory. Plasma protein binding can exert a significant influence on the pharmacokinetic properties and biological activities of a drug, especially for brain-targeted compounds (Raub et al, 1993). For DADLE and its prodrugs, more lipophilic compounds had higher fractions bound in the order CA-DADLE Ͼ OMCA-DADLE Ͼ AOA-DADLE Ͼ DADLE, but none of the prodrugs had protein-binding values high enough to substantially affect the distribution of the compounds.…”
Section: Discussionmentioning
confidence: 99%
“…After intravenous administration, this happens to be the vascular endothelial cell. Indeed, tirilazad has bcen shown to have high affinity for vascular endothelial cells in vitro (26) and to penetrate the intact blood-brain banicr (BBB) very poorly in vivo (27). Although a high degree of binding of tirilazad to impermeable plasma proteins contributes to the limited BBB penetration, further in vitro studies with canine kidney epithclial monolayers (which display diffusional characteristics similar to brain endothclium) have confirmed that the compound has limited transcellular pcrmcability and tcnds to bccome highly concentrated in.…”
Section: Tirilazad Preservation Of Ionic Homeostasismentioning
confidence: 99%
“…Tirilazad mesylate is a 21-aminosteroid that has been shown to inhibit lipid peroxidation in experimental animals (14). Tirilazad mesylate penetrates the intact bloodbrain-barrier poorly but has a strong affinity for the vascular endothelium (21). One randomized clinical study investigating the effect of tiralazad mesylate in the setting of TBI has been reported (22).…”
Section: Aminosteroidsmentioning
confidence: 99%